ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI DIVIDEND PAYOUT RATIO (STUDI PADA PERUSAHAAN NON-KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Asma Mutia; Nurhalis Nurhalis (Departemen Manajemen, 2019)
This study aims to analyze the effect of free cash flow, profitability, leverage, growth rates and company size on dividend payout ratios on non-financial companies listed on the Indonesia Stock Exchange in 2015-2017. Sampling in this study used a puposive sampling technique. The data analysis technique used is multiple linear regression. The results of this study indicate free cash flow, and company size has a positive and significant effect on dividend payout ratio. Profitability, leverage, and growth rates have a negative and significant effect on the dividend payout ratio. Simultaneously free cash flow, profitability, leverage, growth rate, and company size show a significant effect on dividend payout ratio.